Potential feasibility of atezolizumab-bevacizumab therapy in patients with hepatocellular carcinoma treated with tyrosine-kinase inhibitors. Issue 11 (November 2022) - Stefanini, Benedetta; Bucci, Laura; Santi, Valentina; Reggidori, Nicola; Rampoldi, Davide; Lani, Lorenzo; Granito, Alessandro; Sangiovanni, Angelo; Cabibbo, Giuseppe; Farinati, Fabio; Campani, Claudia; Foschi, Francesco Giuseppe; et al.
Abstract: Background: The combination of atezolizumab-bevacizumab has been proven to be superior to sorafenib for the treatment of unresectable hepatocellular carcinoma not amenable to locoregional treatments, becoming the standard of care of systemic therapy. Aim: This study aimed at assessing real-world feasibility of atezolizumab-bevacizumab in patients treated with tyrosine-kinase inhibitors. Methods: Among 1447 patients treated with tyrosine-kinase inhibitors from January 2010 to December 2020, we assessed the percentage of those potentially eligible to atezolizumab-bevacizumab (according to IMbrave-150 trial criteria), and the overall survival of eligible and non-eligible patients. Results: 422 (29%) patients were qualified for atezolizumab-bevacizumab therapy. The main exclusion causes were Child-Pugh class and Performance Status. Adopting the more permissive inclusion criteria of SHARP trial, 535 patients became eligible. The median overall survival of tyrosine-kinase inhibitors patients was 14.9 months, longer in eligible patients than in their counterpart due to better baseline liver function and oncological features. Conclusion: Real-world data indicate that less than one-third of hepatocellular carcinoma patients treated with tyrosine-kinase inhibitors are potentially eligible to atezolizumab-bevacizumab according to the registration trial criteria. These patients have a longer survival than the non-eligible ones. If the selection criteria of atezolizumab-bevacizumab trial are maintained in clinical practice, tyrosine-kinase inhibitors will remain the most used systemic therapy for hepatocellular carcinoma patients.